Urban sprawl: segregation of social housing in Catanduva’s City - Barca, João Victor; Salcedo, Rosio Fernandez Baca; Pasquotto, Geise Brizotti (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Urban sprawl is a phenomenon intrinsically linked to the fragmented expansion process of urban areas. This fact has gained increasing relevance in the contemporary urban context, as cities continue to grow and develop. This sprawl often results in increased car use, infrastructure expansion, consumption of natural resources, and significant environmental impacts. Furthermore, it may have implications for the quality of life of urban dwellers, accessibility to services, infrastructure costs and urban mobility. Therefore, the study of urban sprawl is fundamental to understanding and addressing the challenges associated with urban planning, sustainable development and quality of life in cities. Objective: This article aims to investigate urban expansion and the implementation of housing complexes in the city of Catanduva, located in the northwest of the State of São Paulo. Materials and methods: The methodological aspects for the conception of this study consisted of 3 axes: i) Bibliographic review, ii) Data collection, iii) Development of products for analysis. Results: Based on the collected data, it was found that most of the studied projects present socio-spatial segregation, thus resulting in design guidelines to minimize such aspects.
Keywords: Social Housing; Peripheralization; Urban Sprawl